2022
DOI: 10.1186/s12913-022-08696-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emergency department pharmacists on drug overuse and drug underuse in patients with an ADE-related hospitalisation: a controlled intervention study

Abstract: Background Drug overuse or drug underuse are the most common causes of adverse drug events and can lead to hospital admissions. Using clinical pharmacists in the emergency department may improve patient safety as they are specialised in recognising of adverse drug events and tackling drug overuse and drug underuse. This study tested the effect of an emergency department pharmacist on the number of medication changes for drug overuse and drug underuse taking place in patients with an adverse dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Clinical pharmacists are experts in medicines and their use, and they may through various medication-safety services, such as MedRec, MedRev, medication counseling, patient education and antimicrobial stewardship, optimize medication therapy and resolve medication-related problems [ 12 , 13 ]. Several studies from different countries have shown that ED pharmacists improve medication safety, reduce hospitalization, enhance patient satisfaction and save costs [ 14 , 15 , 16 , 17 ]. The pharmacists’ contribution to the interdisciplinary team can also relieve the other team members of their medication-related tasks and other duties, and reduce their work and cognitive overload [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical pharmacists are experts in medicines and their use, and they may through various medication-safety services, such as MedRec, MedRev, medication counseling, patient education and antimicrobial stewardship, optimize medication therapy and resolve medication-related problems [ 12 , 13 ]. Several studies from different countries have shown that ED pharmacists improve medication safety, reduce hospitalization, enhance patient satisfaction and save costs [ 14 , 15 , 16 , 17 ]. The pharmacists’ contribution to the interdisciplinary team can also relieve the other team members of their medication-related tasks and other duties, and reduce their work and cognitive overload [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%